Creation and validation of a checklist for blood transfusion in children - Carolina Martins Bezerra; Maria Vera Lúcia Moreira Leitão Cardoso; Grazielle Roberta Freitas da Silva; Elisa da Conceição Rodrigues
ABSTRACT Objective: To describe the process for creating and validating a checklist for blood transfusion in children. Method: Methodological study, conducted from November 2016 to May 2017, developed in two stages. The content of the items that compose the instrument was based on scientific evidence and submitted to specialized nurses for content validation. We applied the Content Validity index, considering the value ≥ 0.80. Results: The content was considered valid with global CVI of 0.87. Suggestions for adjustments, such as deletion, replacement, and addition of terms, were included in the final version, which consisted of 14 items and 56 subitems. Conclusion: The checklist for blood transfusion in children was considered a technology with valid content to be used in the transfusion performed by nurses, thus contributing to transfusion safety in children.